Screen-printed carbon electrode modified with poly-L-histidine applied to voltammetric determination of chromium (VI) - Bergamini, Márcio F. [UNESP]; Dos Santos, Daniela P. [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (The Electrochemical Society, 2006)
The present work reports the use of a screen-printed carbon electrode (SPCE) modified by poly-L-histidine film to determine chromium (VI). Stable films can be formed by direct addition of PH solution 1 % (w/v) on the electrode surface, followed by heating at 80°C during 5 min. Calibration curves can be constructed for Cr(VI) from 1.0 × 10-5 mol L-1 to 7.0 × 10-5 mol L-1 Cr (VI) in acetate buffer pH 4 using a preconcentration step of 60s at open circuit potential. A relative standard deviation of 3.2% was for five determination of 4.0 × 10 -5 mol L-1 Cr (VI). The method was successful applied to determination of Cr(VI) in wastewater samples from a leather dyeing industry. copyright The Electrochemical Society.
Keywords: Calibration curves; Screen printed carbon electrode (SPCE); Voltammetric determination; Calibration; Carbon; Dyeing; Electrodes; pH effects; Wastewater; Chromium compounds